Revision of the Australian species of Anatomidae (Mollusca: Gastropoda: Vetigastropoda) - Geiger, Daniel L.; Jansen, Patty (Zootaxa, 2004)
The Australian members of the vetigastropod family Anatomidae are revised and two new species are described. The family has thus far been treated as a subfamily of Scissurellidae, but recent molecular evidence (Geiger & Thacker, unpubl. data) indicates that Scissurellinae plus Anatominaeis not monophyletic, and full family rank is warranted for a group containing the genera Anatoma and Thieleella. Seven species from Australia belonging in Anatomidae are discussed and illustrated by SEM: Anatoma aupouria (Powell, 1937) mainly from New Zealand, though with some Australian records; A. australis (Hedley, 1903), A. funiculata n. sp., An turbinata (A. Adams, 1862), which has been misidentified in the past as the South African A. agulhasensis (Thiele, 1925), A. tobeyoides n. sp., Thieleella equatoria (Hedley, 1899) with a second known specimen, and T. gunteri (Cotton & Godfrey, 1933). Other species that have been (erroneously) indicated from Australia are discussed. A neotype is designated for A. agulhasensis from South Africa for taxon stabilization.